The Impact of Abusive Supervision on Employee Silence- Moderating Role of Power Distance - Bibi Savaira; Dr. Badshah Hussain; Dr. Naveed Farooq (Dialogue Social Science Review (DSSR), 2024)
This research investigates the impact of abusive supervision on employee silence, with the moderating role of power distance in this relationship. Abusive supervision is a sustained pattern of hostile verbal and non-verbal behavior exhibited by supervisors toward their subordinates, which can lead to negative outcomes for both individuals and organizations. This study used a quantitative research design, collecting data from 150 employees working in hospitals located in tehsil Pabbi and in district Nowhere, Pakistan. Validated scales were employed to measure the levels of abusive supervision, employee silence, and power distance. Statistical analyses, including correlation, regression, and moderation analysis were conducted using SPSS to test the relationships among these variables. The findings revealed a strong positive correlation between abusive supervision and employee silence (r = 0.764, p < 0.001), suggesting that employees are more likely to remain silent in response to abusive leadership. Furthermore, power distance was found to moderate this relationship, with the effects of abusive supervision being more pronounced in high power distance contexts. The overall model explained 59.4% of the variance in employee silence, indicating a significant portion of the silence is driven by abusive supervision and moderated by cultural factors like power distance. This study contributes to the understanding of how abusive leadership behaviors impact employee voice and silence, particularly within hierarchical organizational cultures. The findings underscore the importance of addressing abusive supervision through leadership training, policies promoting open communication, and strategies that consider cultural factors such as power distance. Future research needs to explore additional moderators and mediators linkages across different industries and cultural settings. The practical implications of this research suggest that organizations, especially in high power distance cultures, need to adopt a proactive approach to counter the negative effects of abusive supervision. Leadership training programs should focus on fostering collaborative and supportive leadership styles that encourage employee participation and voice.